x2+6x-43=-3

Move 3 to the left side of the equation by adding it to both sides.

x2+6x-43+3=0

Add -43 and 3.

x2+6x-40=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -40 and whose sum is 6.

-4,10

Write the factored form using these integers.

(x-4)(x+10)=0

(x-4)(x+10)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-4=0

x+10=0

Set the first factor equal to 0.

x-4=0

Add 4 to both sides of the equation.

x=4

x=4

Set the next factor equal to 0.

x+10=0

Subtract 10 from both sides of the equation.

x=-10

x=-10

The final solution is all the values that make (x-4)(x+10)=0 true.

x=4,-10

Solve Using the Square Root Property x^2+6x-43=-3